A novel role of BPCs in the control of medial domain differentiation during gynoecium development in Arabidopsis thaliana - Francesca Caselli; Micaela Palermiti; Rosanna Petrella; Veronica Astrid Morlacchi; Kai Dünser; Jűrgen Kleine-Vehn; Matteo Chiara; Veronica Gregis (Plant Molecular Biology, 2026)
The gynoecium, a highly specialized structure in flowering plants, ensures their high reproductive success through the control of different crucial steps spanning from ovule protection to fertilization and seed maturation and dispersion. Multiple bpc mutants show reduced vigor, small fruit size and height, a reduced number of seeds and problems in septum fusion and formation. BPCs are known to be involved in the regulation of key factors involved in plant development, and they are thought to function both as activators and repressors of target gene expression. Here we showed that gynoecium development is affected in different multiple mutants of the Basic PentaCysteine ( BPC ) genes, where the septum fails to develop properly, and that BPCs of class I and II regulate the expression of different genes involved in carpel development and phytohormonal pathways regulation. Considering the fundamental role of the gynoecium, which affects the reproductive success of the plants, we focused on understanding which genes could be putative direct targets of BPCs and thus involved in gynoecium development. We demonstrated that SPATULA and NO TRANSMITTING TRACT ( NTT ), which play pivotal roles in carpel and transmitting tract development, are downregulated. As a consequence, bpc multiple mutants fail to properly develop the septum and the transmitting tract. Interestingly, among the downregulated genes, we also found PIN-LIKES3 , whose promoter can be directly bound by BPCs, which is an auxin efflux carrier that regulates and controls cytoplasmic availability of auxin and could also contribute to various growth processes.

Serum from COVID-19 patients promotes endothelial cell dysfunction through protease-activated receptor 2 - Francesco Vieceli Dalla Sega; Francesca Fortini; Danilo Licastro; Simeone Dal Monego; Margherita Degasperi; Alessia Ascierto; Luisa Marracino; Paolo Severi; Maria D’Accolti; Irene Soffritti; Marta Brambilla; Marina Camera; et al. (Inflammation Research, 2024)

Assessing the role of REM13, REM34 and REM46 during the transition to the reproductive phase in Arabidopsis thaliana - Silvia Manrique; Francesca Caselli; Luis Matías-Hernández; Robert G. Franks; Lucia Colombo; Veronica Gregis (Plant Molecular Biology, 2023)
REM (reproductive meristem) transcription factors have been proposed as regulators of plant reproductive development mainly based on their specific expression patterns in reproductive structures, but their roles are still largely unknown probably because of their redundancy. We selected three REM genes ( REM13 , REM34 and REM46 ) for functional analysis, based on their genome position and/or co-expression data. Our results suggest that these genes have a role in flowering time regulation and may modulate cell cycle progression. In addition, protein interaction experiments revealed that REM34 and REM46 interact with each other, suggesting that they might work cooperatively to regulate cell division during inflorescence meristem commitment. Previous attempts of using co-expression data as a guide for functional analysis of REMs were limited by the transcriptomic data available at the time. Our results uncover previously unknown functions of three members of the REM family of Arabidopsis thaliana and open the door to more comprehensive studies of the REM family, where the combination of co-expression analysis followed by functional studies might contribute to uncovering the biological roles of these proteins and the relationship among them.

Incidence of colonization and bloodstream infection with carbapenem-resistant Enterobacteriaceae in children receiving antineoplastic chemotherapy in Italy - Desiree Caselli; Simone Cesaro; Franca Fagioli; Francesca Carraro; Ottavio Ziino; Giulio Zanazzo; Cristina Meazza; Antonella Colombini; Elio Castagnola (Infectious Diseases, 2016)